Biopsychosocial repercussions in parents who have a child with hemophilia - Osorio G., Maricela (2017)
Receiving a diagnosis of a chronic condition in family, brings changes and drastic repercussions. Hemophilia is an hereditary chronic hemorrhagic disease that needs specific care The objective of this study was to analyze and describe the multidimensional family impact of the hemophilia diagnosis in pediatric patients in a group of progenitors. Attended by 20 parents (10 males and 10 females) answering the PedsQL ™ 2.0 instrument. The Family Impact Module developed by Varni et al., (2004). The low overall scores indicate a biopsychosocial affectation of the parents; the most affected area is the concern and the main physical repercussions are : insomnia, headaches and stomach ache. It is necessary to highlight these problems and design integral care programs for parents.